Electrochemistry of vanadium(II) and the electrodeposition of aluminum-vanadium alloys in the aluminum chloride-1-ethyl-3-methylimidazolium chloride molten salt - Tsuda T.; Hussey C.L. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2003)
The electrochemical behavior of vanadium(II) was examined in the 66.7-33.3 mole percent aluminum chloride-1-ethyl-3-methylimidazolium chloride molten salt containing dissolved VCl2 at 353 K. Voltammetry experiments revealed that V(II) could be electrochemically oxidized to V(III) and V(IV). However at slow scan rates the V(II)/V(III) electrode reaction is complicated by the rapid precipitation of V(III) as VCl3. The reduction of V(II) occurs at potentials considerably negative of the Al(III)/Al electrode reaction, and Al-V alloys cannot be electrodeposited from this melt. However electrodeposition experiments conducted in VCl2-saturated melt containing the additive, 1-ethyl-3-methylimidazolium tetrafluoroborate, resulted in Al-V alloys. The vanadium content of these alloys increased with increasing cathodic current density or more negative applied potentials. X-ray analysis of Al-V alloys that were electrodeposited on a rotating copper wire substrate indicated that these alloys did not form or contain an intermetallic compound, but were non-equilibrium or metastable solid solutions. The chloride-pitting corrosion properties of these alloys were examined in aqueous NaCl by using potentiodynamic polarization techniques. Alloys containing ~10 a/o vanadium exhibited a pitting potential that was 0.3 V positive of that for pure aluminum.